Pengaruh Harapan Kerja, Persepsi, Karakteristik Pribadi terhadap Minat Mahasiswa Memilih Jurusan Akuntansi di Universitas Tadulako - Moh Noviar Lawasa; Nurhaniva A; Nina Yusnita Yamin; Rahayu Indriasari; Andi Chairil Furqan (Akuntansi, 2024)
This study aims to determine and analyze the effect of job expectations, perceptions, personal characteristics on student interest in choosing an accounting major at Tadulako University. This type of research uses descriptive quantitative,. Data collection methods by distributing questionnaires to respondents. The population of this study amounted to 225 active students of class 2021 and 252 active students of class 2022, the number of samples taken was 82 respondents. The analysis method used is multiple linear regression method with the help of SPSS for windows version 25.0. The results showed that work expectations affect student interest in choosing an accounting major, perceptions have no effect on student interest in choosing an accounting major, personal characteristics affect student interest in choosing an accounting major.